The influence of number sense ability and matching item ability towards arithmetic achievement among linus pupils in South-West schools in Sabah - Donorich Joseph Anson (2014)
What predicts children's mathematical achievement? There are so many mathematical abilities that may have influence the arithmetic achievement of a child. The purpose of this study is to determine the influence of number sense ability and matching item ability towards arithmetic achievement of 164 LINUS pupils in South-West schools in Sabah. This study subscribed to the quantitative approach and utilizes the Statistical Package for Social Sciences (SPSS) version 20 in data analysis. The study reveals that there is a significant contribution of number sense ability and matching item ability towards arithmetic achievement of the LINUS pupils (F (2,161) = 4.920, p < 0.05). These mathematical abilities are contributing to approximately 6% of the arithmetic achievement of the LINUS pupils (I = 0.058). These results provide beneficial insights to the policy makers and teachers in incorporating of these abilities into the school's curriculum and mathematics lesson.